2021
DOI: 10.1016/j.asmr.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Versus Open Rotator Cuff Repair: Fellowship-Trained Orthopaedic Surgeons Prefer Arthroscopy and Self-Report a Lower Complication Rate

Abstract: Purpose: To evaluate whether fellowship training had an effect on the practice pattern and complication rates among Part II examinees of the American Board of Orthopaedic Surgery (ABOS) for rotator cuff repair (RCR) from 2007-2017. Methods: The ABOS database was queried for arthroscopic (Current Procedural Terminology [CPT] code 29827) and open/mini-open (CPT codes: 23410, 23412) RCR performed from 2007-2017. Excluded were procedures that did not included CPT codes 29827, 23410, 23412. A comparison between art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The results of one study showed that the surgeons fellowship specialty and complication rates were as follows: Sports Medicine (11.5%), Shoulder and Elbow (13.5%), and Hand and Upper Extremity (13.4%). Surgeons completing a fellowship in Sports Medicine, Shoulder and Elbow or Hand and Upper Extremity all had lower complication rates using the AR approach in comparison to the OR (p < 0.001)[5]. Since their comfort is based on the training and volume they participate in, one could infer that additional studies should be done on the efficiency of open versus arthroscopic repair in surgeons of this caliber of training.…”
mentioning
confidence: 99%
“…The results of one study showed that the surgeons fellowship specialty and complication rates were as follows: Sports Medicine (11.5%), Shoulder and Elbow (13.5%), and Hand and Upper Extremity (13.4%). Surgeons completing a fellowship in Sports Medicine, Shoulder and Elbow or Hand and Upper Extremity all had lower complication rates using the AR approach in comparison to the OR (p < 0.001)[5]. Since their comfort is based on the training and volume they participate in, one could infer that additional studies should be done on the efficiency of open versus arthroscopic repair in surgeons of this caliber of training.…”
mentioning
confidence: 99%